Financial Development and Economic Growth; Evidence from Asia-Pacific Countries - Taufiq Marwa; Muizzuddin Muizzuddin; Imam Asngari (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This research examines the impact of financial development on economic growth. Using a sample of 152 observations from 13 countries in the Asia Pacific for the period 2004 and 2020, we find that financial development positively impacts economic growth, supporting the finance-growth hypothesis, especially in the development of the capital market sector. This research provides policy implications that positive relationship between financial development and growth suggests that policymakers should take the necessary moves towards the simultaneous development of both the banking sector and the stock market to stimulate growth.